Comparison of starch-based liquid sugar production from local cassava - SUKURIYATI SUSILO DEWI; GATOT SUPANGKAT; TRI HASTOMO (Asian Journal of Agriculture, 2025)
Abstract. Dewi SS, Supangkat G, Hastomo T. 2025. Comparison of starch-based liquid sugar production from local cassava. Asian J Agric 9: 683-688. Indonesia's rising sugar demand and dependence on imports have sparked interest in alternative sweeteners sourced from local crops. The country currently imports a significant portion of its sugar, leading to concerns about food security and economic stability. Cassava (Manihot esculenta), widely cultivated across the country, offers a promising raw material for liquid sugar production due to its high starch content and accessibility. This study evaluates the suitability of three cassava varieties; Cartiva 25, Melati, and Randu for liquid sugar production using enzymatic hydrolysis. The process involved liquefaction with ?-amylase followed by saccharification with glucoamylase. Carbohydrate content in the resulting liquid sugar ranged from 76.15 to 80.39%, with Randu and Melati outperforming Cartiva 25. Reducing sugar levels was highest in Randu (65.10%), indicating more efficient starch conversion. Sensory analysis revealed that Randu produced the sweetest and lightest-colored liquid sugar. However, none of the samples met Indonesian National Standards for colorlessness and odorlessness due to the absence of purification steps. While starch yield did not differ significantly among varieties, biochemical and sensory profiles suggest that varietal selection plays a critical role in optimizing sugar output and product quality. Randu and Melati varieties demonstrated superior performance and are recommended for industrial-scale processing. To meet national standards and enhance market viability, future production should incorporate purification techniques such as decolorization and deodorization. These findings offer practical guidance for processors and farmers, highlighting cassava's potential to reduce reliance on imported sugar and support sustainable agriculture. Promoting high-performing varieties like Randu and Melati could strengthen local supply chains and contribute to Indonesia's food system resilience.